Analysis of the Role of Internet of Things in Supporting Social Innovation and Digital Equity: A Multidisciplinary Approach in Digital Society - Fithriawan Nugroho; Dimas Ridho Aldiansyah; Aidil Adhan (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2026)
The development of digital society has driven the adoption of Internet of Things (IoT) technology as a solution to address various social problems. This study aims to analyze the role of IoT in supporting social innovation and to identify the challenges that affect its implementation effectiveness within the context of digital equity. The research employs a qualitative approach using a literature review and thematic analysis of scientific sources published over the past ten years. This study also adopts a multidisciplinary approach that integrates technological, social, and policy perspectives to obtain a comprehensive understanding. The findings indicate that IoT plays a significant role in enhancing the quality of social innovation through real-time data collection, improved service efficiency, and strengthened data-driven decision making. However, the implementation of IoT still faces challenges such as the digital divide, data security risks, and limited technological literacy. This study concludes that the success of IoT is determined not only by technological aspects but also by ecosystem readiness, including infrastructure, policy, and human resource capacity. Therefore, integrative strategies are required to achieve inclusive and sustainable social innovation.